An review of alkylating-like agents in reducing mortality of cancer patients: structure & synthesis - Bahar, Nazia Binta (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.